2019
DOI: 10.1111/cid.12834
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiographic outcomes of allogeneic block grafts for maxillary lateral ridge augmentation: A randomized clinical trial

Abstract: Background A main drawback of bone block graft surgery is the resorption occurring in early stages of healing. To our knowledge, there are no studies comparing outcomes of freeze‐dried bone allograft (FDBA) blocks with different architecture. Purpose The aim of this work was to investigate different factors that can affect graft resorption and to compare the resorption rates of two different types of allogeneic blocks, corticocancellous and cancellous. Materials and Methods A randomized clinical trial was desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 60 publications
3
10
0
Order By: Relevance
“…A total of 11 studies used the staged GBR approach only [16, 18-20, 27-29, 31-34], two studies included both staged and simultaneous GBR [17,35], and the remaining ten studies performed GBR with simultaneous implant placement [21-26, 30, 36-38]. Onlay grafts were used in eight studies, of which six studies obtained grafts from intra-oral donor sites (ramus/symphysis/zygoma) [16, 18-20, 29, 34], one used extra-oral donor sites (iliac crest) [31], while the remaining study used a xenograft (deproteinised bovine bone mineral (DBBM)) block [26]. The most commonly used particulate bone substitute material in the included studies was DBBM.…”
Section: Surgical Procedures and Biomaterials Usedmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 11 studies used the staged GBR approach only [16, 18-20, 27-29, 31-34], two studies included both staged and simultaneous GBR [17,35], and the remaining ten studies performed GBR with simultaneous implant placement [21-26, 30, 36-38]. Onlay grafts were used in eight studies, of which six studies obtained grafts from intra-oral donor sites (ramus/symphysis/zygoma) [16, 18-20, 29, 34], one used extra-oral donor sites (iliac crest) [31], while the remaining study used a xenograft (deproteinised bovine bone mineral (DBBM)) block [26]. The most commonly used particulate bone substitute material in the included studies was DBBM.…”
Section: Surgical Procedures and Biomaterials Usedmentioning
confidence: 99%
“…The most commonly used particulate bone substitute material in the included studies was DBBM. A majority of the studies also used resorbable collagen barrier membranes [16-30, 32, 34-38], three used a nonresorbable expanded polytetrafluoroethylene (ePTFE) membrane [21,22,33], one used a resorbable polylactic (PLA) membrane [24], and one used a plasma rich in growth factors (PRGF) membrane [31].…”
Section: Surgical Procedures and Biomaterials Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…Through micro-CT scanning and histological analysis of 8 weeks after operation, it was found that both of them continued to form new bone, verifying their good osteoinduction and osteogenic ability. In recent years, many researchers have also confirmed that decalcified freeze-dried allogeneic bone has growth factors to promote bone induction, which can aggregate MSCs and support osteoblast differentiation (Clark et al, 2019;Tresguerres et al, 2019). Thus, it has been the only biomaterial approved by the Food and Drug Administration (FDA) in North America for clinical bone repair (Soardi et al, 2012).…”
Section: Allogeneic Bonementioning
confidence: 99%
“…To reduce such loss of bone mass to a reasonable extent, several approaches for the augmentation of absorbed alveolar ridge have emerged over the years . Ridge augmentation for horizontal alveolar ridge deficiency, as one of the reliable methods to surmount the Cawood‐Howell class IV defect, is regularly achieved by applying guided bone regeneration (GBR) technique including the use of xenogenic bone substitute materials and an absorbable membrane.…”
Section: Introductionmentioning
confidence: 99%